2017
DOI: 10.1080/13102818.2017.1281761
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol inhibits quorum sensing and biofilm of toxigenic MRSA strains isolated from food handlers employed in Saudi Arabia

Abstract: Food handlers are important component in assessment and maintenance of food quality as they are carriers of food pathogens causing spoilage. Food spoilage is attributed to quorum sensing (QS) controlled development of biofilms. Therefore, there is an urgent need to develop novel QS and biofilm inhibitors to prevent spoilage of food products. In the present study, toxin producing biofilm forming methicillin-resistant Staphylococcus aureus (MRSA) were isolated from food handlers. Further, eugenol was screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Therefore, some compounds, such as p-anisaldehyde can act as AHL mimics, inhibiting the production of violacein by C. violaceum [84]. Eugenol inhibits QS in pathogenic bacteria; this was shown, for example, by Zhou and co-workers [85], evaluating the reduction of violacein production in C. violaceum after contact with eugenol. This molecule is also capable to affect lasB and pqsA in E. coli.…”
Section: Effect Of Essential Oils On Microbial Cells (Modified Frommentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, some compounds, such as p-anisaldehyde can act as AHL mimics, inhibiting the production of violacein by C. violaceum [84]. Eugenol inhibits QS in pathogenic bacteria; this was shown, for example, by Zhou and co-workers [85], evaluating the reduction of violacein production in C. violaceum after contact with eugenol. This molecule is also capable to affect lasB and pqsA in E. coli.…”
Section: Effect Of Essential Oils On Microbial Cells (Modified Frommentioning
confidence: 95%
“…Among phenols present in the EOs, eugenol at subinhibitory concentrations is capable of inhibiting the production of virulence factors, involving production of violacein and pyocyanin, synthesis and expression of elastase, and finally the organization of the biofilm. In fact, using two E. coli biosensors, MG4/pKDT17 and pEAL08-2, Zhou and co-workers demonstrated that also this compound could act of one or more QS systems, in particular on las and pqs QS systems [85]. The process applied for the extraction of the EO may affect its biological activity indeed.…”
Section: Effect Of Essential Oils On Microbial Cells (Modified Frommentioning
confidence: 99%
“…In this system, LuxI homolog catalyzes AHL formation by forming an amide bond between an acyl side chain of an acyl‐carrier‐protein (acyl ACP) and homoserine of S‐adenosylmethionine (Al), and then AHLs bind to LuxR homolog, forming binary complexes to activate the transcription of downstream genes (Chang et al., 2014). Some examples are the CviI/CviR in Chromobacterium violaceum and CqsA/CqsS in V. cholerae (Al‐Shabib, Husain, Ahmad, & Baig, 2017; Martin‐Rodriguez et al., 2015). At present, the QS system (Figure 3) is more deeply understood in P. aeruginosa , which harbors four types of QS systems, including two LuxI/LuxR‐type (LasI/LasR and RhlI/RhlR) systems, a pseudomonas quinolone signal (PQS) system, and an integrating quorum sensing signal (IQS) system, all of which influence almost 10% of gene expression in P. aeruginosa , constituting a hierarchical regulatory network (Shrikant & Chandrajit, 2018).…”
Section: Bacterial Toxinsmentioning
confidence: 99%
“…Moreover, eugenol reduces the expression of icaD and sarA by 6.1‐ and 8.8‐fold, respectively, in methicillin‐resistant S. aureus (Dhanawade, Kalorey, Srinivasan, Barbuddhe, & Kurkure, 2010; Yadav et al., 2015). A further molecular docking analysis suggests the formation of hydrogen bonds and hydrophobic interaction between eugenol and key residues (L153, K154) in SarA protein (Al‐Shabib et al., 2017).…”
Section: Bacterial Biofilmmentioning
confidence: 99%
“…There are a few studies about the antibiofilm activity of eugenol and pulegone for evaluating their clinical usage. Al-Shabib et al (4) reported eugenol as a broadspectrum anti-quorum sensing and antibiofilm agent against toxin producing biofilm forming methicillinresistant Staphylococcus aureus (MRSA). In a study of Upadhyay et al (40), it is suggested that eugenol could potentially be used to control Listeria monocytogenes biofilms in food processing environments.…”
Section: Discussionmentioning
confidence: 99%